Answer:
x = 3
Step-by-step explanation:
Simplifying
4 + -7x = 1 + -6x
Solving
4 + -7x = 1 + -6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '6x' to each side of the equation.
4 + -7x + 6x = 1 + -6x + 6x
Combine like terms: -7x + 6x = -1x
4 + -1x = 1 + -6x + 6x
Combine like terms: -6x + 6x = 0
4 + -1x = 1 + 0
4 + -1x = 1
Add '-4' to each side of the equation.
4 + -4 + -1x = 1 + -4
Combine like terms: 4 + -4 = 0
0 + -1x = 1 + -4
-1x = 1 + -4
Combine like terms: 1 + -4 = -3
-1x = -3
Divide each side by '-1'.
x = 3
Simplifying
x = 3
multiply the bottom then divide by the top
Answer:
34+x, 2a, m-4, x÷12
Step-by-step explanation:
1) 34+n =
34 + number
2) 2a =
2 x Apple
3) m-4 = a
mary - 4 = age
4)
x÷12
Answer:
y = 1/3 x + 14/3
Step-by-step explanation:
We can identify the two points shown easily.
They are (-2, 4) and (4, 6).
First, we find the line of the slope of the line that contains those two points.
slope = m = (y2 - y1)/(x2 - x1) = (6 - 4)/[4 - (-2)] = 2/6 = 1/3
Now we use one point and the slope to find the y-intercept.
y = mx + b
Let's use point (4, 6) and the slope, 1/3.
6 = (1/3)(4) + b
18/3 = 4/3 + b
b = 18/3 - 4/3
b = 14/3
The equation is
y = mx + b
y = 1/3 x + 14/3